2018
DOI: 10.1109/tvt.2017.2787548
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Joint Source Coding and Trellis Coded Modulation for Symbol-Based Markov Sources

Abstract: A distributed joint source-channel coding scheme based on a unity-rate code (URC)-assisted trellis coded modulation (TCM) is proposed, which exploits the spatio-temporal correlation of symbol-based sources. More specifically, asymmetric distributed source coding of two spatially correlated Markov sources is considered, where one of the sources is assumed to be perfectly decoded and to be available at the receiver of the other source as side information. In order to exploit the temporal correlation statistics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…BER performance of the proposed scheme estimating both the spatial and temporal correlation parameters, spatial correlation parameter only, and without estimating any correlation parameter when there is no knowledge (NK) of the correlation parameters at the receiver as compared to the ideal system with perfect knowledge (PK) of the correlation parameters at the receiver after 20 iterations for sources having p = q = 0.6 and p = q = 0.8. The vertical lines indicate the associated capacities [5], [10].…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…BER performance of the proposed scheme estimating both the spatial and temporal correlation parameters, spatial correlation parameter only, and without estimating any correlation parameter when there is no knowledge (NK) of the correlation parameters at the receiver as compared to the ideal system with perfect knowledge (PK) of the correlation parameters at the receiver after 20 iterations for sources having p = q = 0.6 and p = q = 0.8. The vertical lines indicate the associated capacities [5], [10].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Hence, the authors of [8]- [10] exploited the spatio-temporal correlation of the sources and demonstrated that further performance improvements can be achieved by exploiting both the spatial and temporal correlations, as compared to spatial correlation only.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the attainable performance gain when activating such decoding iteration would be limited in the block fading channel environment [17], as the channel coding itself cannot considerably improve the Bit Error Ratio (BER) [18]. Recently, two spatially correlated Markov sources based transmission was supported using DJSC scheme in [19]. Additionally, a novel lattice-based coding algorithm was proposed in [20], which shows a robust transmission over noisy channel.…”
Section: Introductionmentioning
confidence: 99%